Gambiranom Dance as a Culturally Constructed Aesthetic Behavior of Falling in Love in Javanese Tradition - Paimin Paimin; Sriyadi Sriyadi; Nur Rokhim; Dwiyasmono Dwiyasmono; Sumargono Sumargono (RIRAI Publisher, 2026)
Love-themed dance repertoires occupy a significant position in the Surakarta dance tradition as cultural representations of emotional experience and Javanese values. Among these repertoires, Gambiranom represents the theme of gandrungan through a male solo dance that articulates the protagonist’s psychological experiences of longing, affection, and determination in the pursuit of love. Although previous studies have examined its choreographic structure and performance form, limited attention has been given to its movement vocabulary as culturally constructed aesthetic behavior. This study investigates how aesthetic behavior in Gambiranom is shaped by the emotional experiences and everyday practices of Javanese society and embodied through its performance style. Employing a qualitative research design with an ethnochoreological approach, data were collected through participant observation supported by a literature study and analyzed through data reduction, categorization, interpretation, and conclusion drawing. The findings demonstrate that the movement vocabulary of Gambiranom is not arbitrarily composed but derives from the stylization of everyday behaviors associated with the experience of falling in love, including longing, affection, self-grooming, emotional intimacy, and the determination to unite with one’s beloved. These behaviors are transformed into aesthetic behavior through the choreographic conventions of Javanese dance and embodied in the kiprahan performance model with a putra alus lanyap performance style. The study concludes that aesthetic behavior in Gambiranom functions not only as a choreographic convention but also as a cultural identity through which Javanese society constructs and communicates the experience of romantic love within the tradition of ethnic dance.